1999
DOI: 10.1107/s0021889898016501
|View full text |Cite
|
Sign up to set email alerts
|

K2(NbO)2Si4O12: a new ferroelectric

Abstract: The atomic coordinates of K2(NbO)2Si4O12 reported in space group P4bm satisfy the structural criteria for ferroelectricity. The estimated phase‐transition temperature, Tc = 2230 (250) K, is substantially in excess of Tmelting = 1476 (5) K; the hypothetical paraelectric phase in space group P4/mbm is hence experimentally inaccessible. A strong indication that the phase transition does not occur at T < Tmelting is provided by the absence of both calorimetric and dielectric permittivity anomalies below Tmelting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…The estimated P s value was substantially lower than the previously-reported value of 5¯C/cm 2 for KNbSi 2 O 7 ceramics. 1) On the other hand, the estimated E c value was considerably higher than the previously-reported value of 0.7 kV/cm. These results suggested that the low P s value for KNbSi 2 O 7 single crystal is caused by the difficulty in polarization switching of single domain state due to the high coercive field.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…The estimated P s value was substantially lower than the previously-reported value of 5¯C/cm 2 for KNbSi 2 O 7 ceramics. 1) On the other hand, the estimated E c value was considerably higher than the previously-reported value of 0.7 kV/cm. These results suggested that the low P s value for KNbSi 2 O 7 single crystal is caused by the difficulty in polarization switching of single domain state due to the high coercive field.…”
Section: Resultscontrasting
confidence: 65%
“…4) They fabricated KNbSi 2 O 7 polycrystalline ceramics and measured the polarization-electric field (P-E) hysteresis of the ceramics. The anisotropies of dielectric and ferroelectric properties of KNbSi 2 O 7 remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The natural analog of the tetragonal synthetic phase KNbSi 2 O 7 , a new structural type among natural K-Nb-cyclosilicates, named rippite, was discovered in calciocarbonatites of the Chuktukon massif, Chadobets upland, SW Siberian Platform, Krasnoyarsk Territory, Russia [ [4]. It is rather inert and chemically stable and is not dissolved in inorganic acids except HF.…”
Section: Introductionmentioning
confidence: 99%
“…It is rather inert and chemically stable and is not dissolved in inorganic acids except HF. All studies on KNbSi 2 O 7 are mainly focused on its nonlinear optical property [3][4][5][6][7][8][9][10][11][12][13][14][15]. Single crystals, ceramics, glass-ceramics, and glass of KNbSi 2 O 7 and similar compositions in the systems SiO 2 (±GeO 2 )-Nb 2 O 5 -K 2 O have been fabricated [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation